2021
DOI: 10.3390/ijerph182312335
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Lifestyle and Prevention among Adolescents with Idiopathic Juvenile Scoliosis: A Cross Sectional Study in Eleven First-Grade Secondary Schools of Palermo Province, Italy

Abstract: Adolescent idiopathic scoliosis (AIS) has an incidence of 2–3% in the general population and a multifactorial etiology. The present study aims to analyze modifiable risk factors and their interactions in the development of AIS in order to increase knowledge about the disease and to prevent the evolution of AIS in young students with tailored public health strategies. A cross-sectional study was conducted over two consecutive school years among students attending 11 first-grade secondary schools in the province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
3
16
1
1
Order By: Relevance
“…Idiopathic scoliosis has a high incidence among children all over the world and its multifactorial etiology is now accepted, although to date it is not fully known [ 16 , 23 , 27 , 28 ]. This condition can lead to important changes in the child’s physical appearance with a negative psychological effect on it [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Idiopathic scoliosis has a high incidence among children all over the world and its multifactorial etiology is now accepted, although to date it is not fully known [ 16 , 23 , 27 , 28 ]. This condition can lead to important changes in the child’s physical appearance with a negative psychological effect on it [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is little clarity on the possible risk factors for idiopathic scoliosis, as the results appear quite conflicting [ 16 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though few studies suggested that spinal fusion surgery may not generate severe impairment afterward [6,7], the benefit of surgery is still controversial and more than 500 million dollars per year are spent in the United States alone on AIS surgeries [7,8]. Thus population-based screening and proper treatment at the onset of disease to prevent curve progression will not only improve AIS patients' health outcomes but also save healthcare dollars [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…AIS is accompanied by different risk factors, such as growth disturbances, postural disorders, environmental factors, visual and dental disorders, etc. [ 7 , 8 , 9 ]. AIS may also be related to high-risk sports (ballet, rhythmic gymnastics, swimming, some athletic activities, etc.)…”
Section: Introductionmentioning
confidence: 99%